Pathological upstaging detected in radical cystectomy procedures is associated with a significantly worse tumour-specific survival rate for patients with clinical T1 urothelial carcinoma of the urinary bladder - May, Matthias; Bastian, Patrick J.; Brookman-May, Sabine; Burger, Maximilian; Bolenz, Christian; Trojan, Lutz; Michel, Maurice Stephan; Herrmann, Edwin; Wülfing, Christian; Tiemann, Arne; Müller, Stefan C.; Ellinger, Jörg; et al. (Scandinavian journal of urology and nephrology, 2011)
Objective. Due to their variable oncological course, clinical stage T1 (cT1) urothelial carcinomas of the bladder (UCBs) are the subject of controversial discussion with regard to indication for radical cystectomy (RC).This study aimed to evaluate the frequency and prognosis of upstaging in patients undergoing RC due to UCB. Material and methods. Clinical and pathological records of 607 patients, having undergone RC for treatment of UCB in cT1N0M0, were summarized in a multi-institutional database. Cancer-specific survival (CSS) and overall survival (OS) rates were calculated. A multivariable prognostic model predicting the possibility of an upstaging in RC specimens was developed based on clinical information. Results. In 210patients (35%) an upstaging (> pT1 and/or pN+) was detected in the RC specimen. Five-year CSS was 86%, 78%, 60%and 34%, respectively, for tumour stages < pT2N0 (n = 397), pT2N0 (n = 78), > pT2N0 (n = 63)and pN+ (n = 69) (p < 0.001). In a multivariable Cox regression model, pN stage, pT stage and lymphovascular invasion (LVI) revealed an independent influence on CSS (OS: pN, pT, age). An upstaging of cT1 tumours was enhanced by the criteria of G3 tumour grading and absent Tis in the transurethral resection of the bladder (TURB)specimen. Detection of LVI in RC specimens was also independently associated with an upstaging and, therefore, is recommended as a relevant prognostic parameter for the histopathological evaluation of TURB specimens. Conclusions. More than one-third of patients with cT1 tumours had an upstaging that was associated with significant prognosis deterioration. Further valid markers are required for an early identification of these patients. LVI represents such a criterion and, therefore, should be evaluated in prospectively designed trials with accurate histopathological assessment of TURB specimens.
Gesehen am 12.08.2022